Principal's Decision, Organizational Commitment, and Organizational Climate in Influencing the Performance of Vocational High School Teachers - Ru'yat, Ru'yat; Pogo, Tajuddin (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – The purpose of this study was to determine the effect of principal's decision making, organizational commitment, organizational climate on teacher performance at Private Vacational High School Kota Tangerang Methodology/approach – This research is causal quantitative with survey method used in data collection. The population is a private vocational school teacher in Tangerang City with a sample of 100 respondents using a random sampling technique. Findings – The results showed that 1) There is an influence of Decision Making on Teacher Performance, with the interaction between school principals and teachers in making decisions to be a big influential indicator. 2) There is an influence of Organizational Commitment on Teacher Performance, with commitment to career development according to the period of service being an indicator of great influence. 3) There is an influence of Organizational Climate on Teacher Performance, with the principal's efforts to encourage teachers to foster gifted students being a big influential indicator. Novelty/value – The interaction between the principal and the teacher in making decisions is a major indicator of influence, so the principal should be able to maintain interaction with teachers in order to decide on appropriate policies for the progress and improvement of teacher performance in schools. Then, career development according to the period of service is a big indicator of organizational commitment, it is necessary to have talent management in this case the teacher and the right career succession so that it can improve teacher performance. Finally, the coaching of gifted students in this study is alleged to have a major influence on the creation of a good organizational climate, talented students are expected to become good influencers for schools so that the school's learning situation and climate will be good and teacher performance will increase because the students are talented.